Fetoscopic laser coagulation for twin–twin transfusion syndrome before 17 weeks' gestation: laser data, complications and neonatal outcome. (September 2014) - Lecointre, L.; Sananes, N.; Weingertner, A. S.; Kohler, M.; Guerra, F.; Fritz, G.; Viville, B.; Langer, B.; Nisand, I.; Favre, R.
ABSTRACT Objective To compare laser data, complications and neonatal outcome in pregnancies that undergo 'early' (≤ 17 weeks' gestation) fetoscopic laser ablation of placental vascular anastomoses for twin–twin transfusion syndrome (TTTS) with those from 'conventional' cases treated after 17 weeks. Methods This was a cohort study of data collected prospectively between January 2004 and December 2012. We included monochorionic diamniotic twin pregnancies complicated by TTTS and treated by fetoscopic laser coagulation. Pregnancies were grouped according to laser treatment ≤ 17 gestational weeks or > 17 weeks and obstetric and neonatal outcomes were compared between groups. Results A total of 178 pregnancies with TTTS underwent laser therapy: 40 at or before 17 weeks and 138 after 17 weeks. There was no statistically significant difference between these two groups with respect to the rate of preterm prelabor rupture of membranes (PPROM), gestational age at PPROM and rate of PPROM occurring in the 7 days following fetoscopic laser coagulation. In the early group, the interval between performing fetoscopic laser coagulation and the time of delivery was significantly longer (104 days vs 74 days, P = 0.0002) and the delivery rate within 7 days of laser treatment was significantly lower (2.5% vs 15.9%, P = 0.026). There was no significant difference between the two groups with regard to the rates of pregnancy without live birth (15.4% vs 15.4%, P = 0.993), with one live birth (84.6% vs 84.6%, P = 0.993) and with two live births (64.1% vs 58.1%, P = 0.500). Conclusion In the event of early TTTS, fetoscopic laser coagulation is technically feasible before 17 gestational weeks and obstetric and neonatal outcomes are comparable with those in cases of laser treatment performed after 17 weeks. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd